2000
DOI: 10.1046/j.1469-8137.2000.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of stomatal conductance with hydraulic and chemical factors in several deciduous tree species in a natural habitat

Abstract: Recent research in whole-plant stomatal physiology, conducted largely with potted plants in controlled environments, suggests that stomatal conductance (g s ) might be more closely linked to plant chemical variables than to hydraulic variables. To test this in a field situation, seasonal g s was examined in relation to a number of plant and environmental variables in 11 temperate, deciduous forest tree species. Stomatal conductance was generally better correlated with environmental variables (air temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…(2001) found, in partly dried split root experiments with bell pepper plants, that stomatal closure is controlled by hydraulic conditions. The situation may be very complicated and results and conclusions, moreover, depend on the applied methods and on investigated species (Augé et al ., 2000), lines, cultivars or clones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2001) found, in partly dried split root experiments with bell pepper plants, that stomatal closure is controlled by hydraulic conditions. The situation may be very complicated and results and conclusions, moreover, depend on the applied methods and on investigated species (Augé et al ., 2000), lines, cultivars or clones.…”
Section: Discussionmentioning
confidence: 99%
“…depend on the applied methods and on investigated species (Augé et al, 2000), lines, cultivars or clones. When the present data set was divided into the provenances, a good correlation was observed between water content and transpiration rate for provenances from prevailing wet habitats (K P > 0.7): 'small', 'sont', 'sees' 'black'.…”
Section: Biometrical Data Transpiration and Predawn Water Potentialmentioning
confidence: 99%
“…The rationale for PRD is based on an understanding of the action of long-distance chemical signalling in plants, but there are concerns that this form of signalling is not universal (Rodrigues et al 2008). Thus in several tree species, g s correlated better with environmental variables such as air temperature, vapour pressure deficit (VPD) and PPFD than with plant variables such as shoot water potential, leaf osmotic potential, turgor, xylem sap pH or [X-ABA] leaf (Augé et al 2000). Relatively few studies have investigated the effect of atmospheric water deficit on longdistance ABA signalling.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand many authors (Chandler and Robertson 1994;Leung and Giradaut 1998) point to the importance of root-originated chemical messengers, particularly ABA, to stomatal closure, and molecular evidence has recently been provided (Lemichez et al 2001). On the other hand, hydraulic and not ABA control of stomatal closure has been reported to be of primary importance for herbaceous (Bunce 1999;Yao et al 2001;Cochard 2002) and woody (Saliendra et al 1995;Fuchs and Livingston 1996;Augé et al 2000;Matzner et al 2001) plants. Moreover, it has recently been shown that aquaporins regulate hydraulic conductance of cell membranes (Morillon and Chrispeels 2001) and plant organs (Siefritz et al 2002).…”
Section: Introductionmentioning
confidence: 99%